Addressing the challenge of bringing evidence in decision-making for public health emergencies: can HTA reach out to preparedness?. (30th September 2020) - de Waure, C; Miglietta, A; Favaretti, C
Abstract: Background: Preparedness is one of the fundamental public health activities as it allows health systems to effectively manage threats. It can be considered a continuous quality improvement process, therefore requiring an assessment both in planning and checking phase. The assessment should consider several aspects spanning contextual factors but also health technologies being used. In order to manage threats, epidemics in particular, several health technologies are generally deployed. Among them, vaccines, antimicrobials, medical devices (i.e. masks), procedures (i.e. quarantine). Indeed, an early and as much as comprehensive evaluation of their value in the mitigation of epidemics' impact is needed. Health Technology Assessment (HTA) could help doing that. It could be also useful to predict the magnitude of the problem and to shed light on alternatives and needs for organizational reengineering. Anyway, what are the actions required to make HTA reaching out preparedness? Results: In order to do it, several conditions should be brought about. The first one is the recognition of the importance of HTA in projecting health technologies impacts by health authorities and institutions. The second one is the timeliness of the assessment. In fact, HTA is generally a time and resource consuming approach as it is based on the collection of available evidence and data. Nevertheless, an early interaction with all stakeholders, the availability of flexible computer infrastructures for data collection and the preventive development of impact models might allow developing the assessment in a limited time. Furthermore, having dedicated working teams at supranational/national level could help keep down time and efforts to conduct the assessment. Conclusions: Based on available experiences, advances and barriers in the use of HTA for preparedness might be highlighted and actions to strengthen the role of HTA in this field can be recognized.